1976
DOI: 10.3402/tellusa.v28i6.11316
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic climate models: Part I. Theory

Abstract: A stochastic model of climate variability is considered in which slow changes of climate are explained as the integral response to continuous random excitation by short period "weather" disturbances. The coupled ocean-atmosphere-cryosphere-land system is divided into a rapidly varying "weather" system (essentially the atmosphere) and a slowly responding "climate" system (the ocean, cryosphere, land vegetation, etc.). In the usual Statistical Dynamical Model (SDM) only the average transport effects of the rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
615
0
5

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,104 publications
(657 citation statements)
references
References 9 publications
32
615
0
5
Order By: Relevance
“…4. In all experiments an overall red-noise behaviour is observed, as expected from the stochastic climate scenario proposed by Hasselmann (1976). The red oceanic spectrum is a consequence of the amplification of lowfrequency weather fluctuations.…”
Section: Models 1-3supporting
confidence: 76%
“…4. In all experiments an overall red-noise behaviour is observed, as expected from the stochastic climate scenario proposed by Hasselmann (1976). The red oceanic spectrum is a consequence of the amplification of lowfrequency weather fluctuations.…”
Section: Models 1-3supporting
confidence: 76%
“…Concerning the low-frequency variations of the NAO on decadal and interdecadal time scales, one important issue is the role of the North Atlantic Ocean. It is broadly accepted that the passive response of the ocean is in agreement with the statistical climate model concept of Hasselmann (1976), but the active role of the ocean on the NAO dynamics is still open to debate. Studies based on observational data have shown that extratropical SST anomalies could force the atmospheric circulation (Czaja and Frankignoul 2002).…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, Earth Models of Intermediate complexity [9,23], which are tailored for such problems, are definitely not competitive if our aim is to describe the variability of the present climate and the short-term climate change. The problem of providing a satisfactory description of the dynamical processes that cannot be explicitly be represented has long been addressed at various levels of rigour by the climate community [20,31,11,10,3,28,22]. The solutions that are being used in practical applications today go by the name of parametrizations.…”
Section: Introductionmentioning
confidence: 99%